Communication Strategy Development of LPP TVRI in Implementing Nawacita and Sustainable Development Goals - Rizky Wulan Ramadhani; Fajar Rizali Rakhman; Edy Prihantoro (MediaTor (Jurnal Komunikasi), 2020)
Indonesia signed the Sustainable Development Goals (SDGs) in 2015. Joko Widodo and Jusuf Kalla proposed Nawacita as a national development goal that must be achieved. Nawacita and SDGs have similarities that involve mass media. TVRI has an extensive network to implement Nawacita and SDGs through a development communication strategy as communication planning and communication management in disseminating messages to invite the community to be involved in development. This study aims to determine the development communication strategy of TVRI in implementing Nawacita and SDGs. Qualitative research methods by conducting interviews and documentation of various sources. From the research results it is known that the media can help to implement Nawacita and SDGs. In this case, TVRI as media that participates in helping the success of the government's role in implementing Nawacita and SDGs in Indonesia using development communication strategies, namely: media-based strategy by using national and local stations, Monitor magazine, new media (website www.tvri.go.id, Instagram @tvrinasional, Twitter @TVRINasional, Facebook TVRI Nasional, Youtube TVRI Nasional and the TVRI Klik application), instructional design strategies (internal and external training), participatory strategies (audience journalism and institutional visits) and marketing strategies (programs and collaborations) that are tailored to the values of Nawacita and SDGs